Analisis Perbedaan Abnormal Return, Trading Volume Activity, Dan Security Return Variability Pada Perusahaan LQ 45 Pra Dan Pasca Pengumuman Kabinet Indonesia Maju Periode 2019-2024 - Aditha, Kadek Krisna; Adiputra, I Made Pradana (Universitas Pendidikan Ganesha, 2020)
The emergence of abnormal returns, trading volume activity, and security return variability that are significantly different can be used as a variable in measuring capital market reactions to information from political announcements. Analyzing whether or not there is a significant difference in the average abnormal return, trading volume activity, and security return variability before and after the announcement of Indonesia Maju cabinet for the 2019-2024 period is the purpose of the study. Data were collected using documentation techniques and analyzed using different tests. The results obtained show that: the average abnormal return, trading volume activity, and security return variability are not significantly different before and after the announcement of Indonesia Maju cabinet for the 2019-2024 period.